Education of Birth Ball Training as Therapy to Relieving Labor Pain - Sitorus, Riris; S, Grace Erlyn Damayanti; Telova, Yurizki; Arisman, Yessy; Liesmayani, Elvi Era (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Labor pain arises because of the mother's physical and psychological response. Emotions become unstable due to anxiety and fear which worsen the condition of labor pain. The pain experienced by the mother during labor can give rise to fear which makes her anxious and often leads to panic attacks. This condition causes a physiological response that can disrupt the condition of the uterus when it contracts so that the impact of labor will last a long time. Usually, the mother who is about to give birth will find it difficult to adjust to the conditions of labor pain, so that uterine contractions cannot be controlled which causes the first stage to lengthen and the fetus to be disturbed. A prolonged labor process is a type of birth complication that is worrying, complicated, and unpredictable. A non-pharmacological method that can reduce labor pain is birth ball therapy. Research that has been conducted has found that birth ball exercises affect reducing labor pain. PkM is implemented through educational activities where there are 30 PkM participants. The results of the PkM implementation show that the PkM participants have been successfully educated through this PkM activity so that they can apply birth ball exercises to reduce labor pain in mothers. Due to the implementation of this PkM activity, it is hoped that there will be an increase in the knowledge of midwives who play a role in initial level services to provide appropriate steps in dealing with labor pain in mothers using complementary therapy, and birth ball exercises.